2014
DOI: 10.3102/0002831214541669
|View full text |Cite
|
Sign up to set email alerts
|

A New Model for Student Support in High-Poverty Urban Elementary Schools

Abstract: Efforts to support children in schools require addressing not only academic issues, but also out-of-school factors that can affect students’ ability to succeed. This study examined academic achievement of students participating in City Connects, a student support intervention operating in high-poverty elementary schools. The sample included 7,948 kindergarten to fifth-grade students in a large urban district during 1999–2009. School- and student-level treatment effects on report card grades and standardized te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 42 publications
2
38
0
1
Order By: Relevance
“…This growth of the intervention was not randomized, but occurred through district interest in expansion. On average, intervention schools were more disadvantaged socioeconomically and had lower student baseline achievement than the district at large (Walsh et al., ). In the present study, 8 of these 13 schools were of special interest, because these 8 schools experienced a change in intervention status at some point between 2001 and 2008, the time frame for which we have student achievement data from a nationally standardized assessment tool (see Measures).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This growth of the intervention was not randomized, but occurred through district interest in expansion. On average, intervention schools were more disadvantaged socioeconomically and had lower student baseline achievement than the district at large (Walsh et al., ). In the present study, 8 of these 13 schools were of special interest, because these 8 schools experienced a change in intervention status at some point between 2001 and 2008, the time frame for which we have student achievement data from a nationally standardized assessment tool (see Measures).…”
Section: Methodsmentioning
confidence: 99%
“…Across 11 experimental and quasi‐experimental studies of four student support intervention models, initial evidence indicates that these programs promote achievement, both reading and math, for children in low‐income families (Moore & Emig, ). For example, in a quasi‐experimental study of approximately 8,000 children who attended high‐poverty elementary schools, those who had attended intervention schools with student support services demonstrated better reading and math test scores later, during middle school, than did children who had attended comparison schools, after adjusting for early achievement and demographics via propensity score weighting (Walsh et al., ).…”
Section: Immigrant Children Growing Up Poormentioning
confidence: 99%
“…Data show that City Connects significantly improves academic performance and thriving, and narrows the achievement gap for low-income students in participating schools (City Connects 2014a; City Connects 2014b; Walsh et al 2014). Students enrolled in City Connects elementary schools outperform their peers who were never enrolled in a City Connects school on measures of academic achievement (i.e., standardized assessments and classroom report cards) and demonstrate improved thriving in areas such as behavior, work habits, and effort (City Connects 2014a; City Connects 2014b; Walsh et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Past quasi-experimental research has demonstrated beneficial effects of City Connects (Dearing, Sibley, Lee-St. John, Raczek, & Walsh 2016;Walsh et al, 2014). The evaluation of the intervention has been designed as a quasi-experiment, because participating schools were identified by the district to receive the full program treatment.…”
Section: Treatmentmentioning
confidence: 99%